1989
DOI: 10.1002/zoo.1430080107
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive biology of female Père David's deer (Elaphurus davidianus)

Abstract: Data for this study came from breeding records of 27 Pbre David's (Elaphurus duvidiunus) hinds maintained in large pastures and from estrous records of four hand-reared nulliparous hinds. The mean estrous cycle length ranged from 17.5 to 19.6 days. Standing estrus resembled that of other cervids, except that a low, moaning vocalization was given in response to contact, and activity (as measured by pedometers) did not increase. Mean gestation length was 183.38 t SD 6.11 days (n = 21), and nearly all females con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…The calving rate of 37.1 per cent in this herd for the 7-year study period is low compared with the report of Wemmer and others (1989) who found that, between 1975 and 1987, a herd of 27 adult Père David's does under similar housing conditions in Virginia demonstrated a calving rate of 89.2 per cent. Interestingly, the coyote population has been estimated to have increased in Ohio fivefold between 1990 and 2011 ( http://wildlife.ohiodnr.gov/species-and-habitats/species-guide-index/mammals/coyote ), and the population of white-tailed deer has grown from an estimated 17,000 in 1970 to 700,000 in 2006 ( http://wildlife.ohiodnr.gov/portals/wildlife-/pdfs/publications/wildlife%20management/pub087.pdf ).…”
Section: Discussioncontrasting
confidence: 70%
“…The calving rate of 37.1 per cent in this herd for the 7-year study period is low compared with the report of Wemmer and others (1989) who found that, between 1975 and 1987, a herd of 27 adult Père David's does under similar housing conditions in Virginia demonstrated a calving rate of 89.2 per cent. Interestingly, the coyote population has been estimated to have increased in Ohio fivefold between 1990 and 2011 ( http://wildlife.ohiodnr.gov/species-and-habitats/species-guide-index/mammals/coyote ), and the population of white-tailed deer has grown from an estimated 17,000 in 1970 to 700,000 in 2006 ( http://wildlife.ohiodnr.gov/portals/wildlife-/pdfs/publications/wildlife%20management/pub087.pdf ).…”
Section: Discussioncontrasting
confidence: 70%
“…In most of the temperate deer species, females are seasonally polyestrous and exhibit the estrous cycles ranged from 17 to 21 days in chital deer (Chapple et al ., 1993), 21 to 26 days in fallow deer (Asher, 1985;Asher et al ., 1986Asher et al ., , 1988, 18 to 21 days in red deer (Adam et al ., 1985;Guinness et al ., 1971;Kelly and Moore, 1977), 22 to 29 days in white-tailed deer (Plotka et al ., 1980;Verme, 1985) or blacktailed deer (Thomas and Cowan, 1975), and 18 to 20 days in the Pere David's deer (Curlewis et al ., 1988;Wemmer et al ., 1989). As observed in the present study, the duration of estrous cycles of the polyestrous FSD hinds, inhabiting in tropical southern Taiwan, based on the consecutive basal progesterone values during the major rutting season, were 19.3 ± 1.8 days.…”
Section: Discussionmentioning
confidence: 99%